(untitled) (Jahangirnagar University Journal of Biological Sciences, 2020)
In a series of two separate studies during January through August 2018, various birth abnormalities (BA) from 178 clinical cases and congenital malformations (CMF) from 70 consanguineous marriages (CM) and 100 non-consanguineous marriages (NCM) within the Rajshahi City Corporation (RCC) area have been recorded, analyzed and interpreted. Results demonstrate that frequencies of miscarriages (5.69 vs. 3.00), stillbirths (3.85 vs. 1.00), postnatal deaths (8.97 vs. 1.00), preterm deliveries (29.49 vs. 38.00) and breech births (6.41 vs. 4.00) were significantly greater in CM compared to the NCM counterparts. In addition, both gestational ages and live birth weights of the children from CM were significantly lesser than those recorded from the NCM couples. Of 205 children derived from 70 CM couples 67 were suffering from various CMF, the remaining 138 children were normal. Compared to this, only 2 out of 267 children were affected from 100 NCM couples. Mental retardation (MR) represented the highest CMF (n= 37), followed by cerebral palsy (CP; n= 16), crossed-eyes (CE; n=4), blindness (BL) and microcephaly (MC; n= 3 each), deaf-mute (DM; n= 2), and Down’s syndrome (DS) and syndactyly (SD; n= 1 each). In contrast to the CM cases, the NCM couples had only two affected children, one crossed-eyed girl and the other polydactylous boy. The overall frequency of CMF in CM (32.68) was much higher than that in NCM cases (0.75). In relation to parental consanguinity, the importance of genetic counselling and pre-implantation screening relevant to the present findings has been emphasized in this report. Jahangirnagar University J. Biol. Sci. 8(2): 81-91, 2019 (December)